Kinetic Resolution of Oxazinones: Rational Exploration of Chemical Space through the Design of Experiments. Issue 37 (30th July 2014) - Renzi, Polyssena; Kronig, Christel; Carlone, Armando; Eröksüz, Serap; Berkessel, Albrecht; Bella, Marco
Abstract The organocatalytic kinetic resolution of 4‐substituted oxazinones has been optimised (selectivity factor S up to 98, chiral oxazinone ee values up to 99.6 % (1 a–g) and product ee values up to 90 % (3 a–g)) in a rational way by applying the Design of Experiments (DoE) approach.